The Pointing Errors in Optic Ataxia Reveal the Role of “Peripheral Magnification” of the PPC - Vindras, Philippe; Blangero, Annabelle; Ota, Hisaaki; Reilly, Karen T.; Rossetti, Yves; Pisella, Laure (Frontiers in Integrative Neuroscience, 2016)
Interaction with visual objects in the environment requires an accurate correspondence between visual space and its internal representation within the brain. Many clinical conditions involve some impairment in visuo-motor control and the errors created by the lesion of a specific brain region are neither random nor uninformative. Modern approaches to studying the neuropsychology of action require powerful data-driven analyses and error modelling in order to understand the function of the lesioned areas. In the present paper we carried out mixed-effect analyses of the pointing errors of seven optic ataxia patients and seven control subjects. We found that a small parameter set is sufficient to explain the pointing errors produced by unilateral optic ataxia patients. In particular, the extremely stereotypical errors made when pointing toward the contralesional visual field can be fitted by mathematical models similar to those used to model central magnification in cortical or sub-cortical structure(s). Our interpretation is that visual areas that contain this footprint of central magnification guide pointing movements when the posterior parietal cortex is damaged and that the functional role of the posterior parietal cortex is to actively compensate for the under-representation of peripheral vision that accompanies central magnification. Optic ataxia misreaching reveals what would be hand movement accuracy and precision if the human motor system did not include elaborated corrective processes for reaching and grasping to non-foveated targets.